Microwave-hydrothermal synthesis of boron/nitrogen co-doped graphene as an efficient metal-free electrocatalyst for oxygen reduction reaction - Kim, Il To; Song, Myeong Jun; Kim, Young Bok; Shin, Moo Whan (International journal of hydrogen energy, 2016)
In this study, a facile microwave-hydrothermal method was successfully applied to synthesize boron and nitrogen co-doped graphene (BNG) electrocatalyst for the oxygen reduction reaction (ORR). It consists of an efficient two-step process involving simultaneous doping with different heteroatoms (B and N) and reduction of doped graphene oxide. It was found that the B and N contents of highly reduced BN co-doped graphene (HRBNG) are 3.55 and 4.43 at%, respectively. The HRBNG exhibited clearly enhanced electrocatalytic activity towards the ORR in alkaline electrolytes. The electron transfer number (n) was obtained 3.53 ∼ 3.84 in potential range of 0.465 V–0.225 V, indicating that the HRBNG favors the four-electron pathway for the reduction of oxygen. These results demonstrate that the synthesized HRBNG has potential to replace expensive precious metal catalysts and also provide a new strategy to synthesize heteroatom-doped graphene-based catalyst. •BN co-doped graphene was synthesized by facile microwave-hydrothermal method.•The method extremely shortens synthesis time.•The catalyst exhibits improved ORR activity in alkaline solution.•The ORR process of the catalyst occurs dominantly through a four-electron mechanism.